Higiene, pueblo y sanidad en Cali. Instituciones, prácticas e imaginarios. 1945-1950 (2015)
There is analyzed how the elites of Cali faced the problem of the hygiene in the middle of the 20th century, in a context of the renovation of the public politics, which was sealed by the redefinition of the place of the “people”; for the processes of industrialization, urbanization and demographic growth and for the consolidation of a medical of the company. From it splits of the supposition of which the practices and institutions about the hygiene in Cali rested essentially on the imaginary one of the defense of the people. These discussions were achieved to rake in the municipal and periodic files of the epoch. These discussions were achieved to rake in the municipal and periodic files of the epoch. A politics that tried to be put into practice in a conjuncture that generated tensions between the old moral trends, the normative codes and the new scientific practices of the public health and of the social medicine.